Business intelligence : 4th European Summer School, eBISS 2014, Berlin, Germany, July 6-11, 2014, Tutorial lectures /: 4th European Summer School, eBISS 2014, Berlin, Germany, July 6-11, 2014, Tutorial lectures. (2015) - Unknown
No abstract available